Controlled‐release iodine foam dressings demonstrate broad‐spectrum biofilm management in several in vitro models. Issue 7 (15th February 2022) - Salisbury, Anne‐Marie; Mullin, Marc; Foulkes, Lauren; Chen, Rui; Percival, Steven L.
Abstract: Multiple in vitro models were utilised to evaluate the biofilm management capabilities of seven commercially‐available wound dressings, varying in composition and antibacterial ingredients, to reduce common aerobic, anaerobic, and multispecies biofilms. The Center for Disease Control bioreactor was used to evaluate single species Pseudomonas aeruginosa ( P. aeruginosa ) and Staphylococcus aureus ( S. aureus ) 24 and 48 hours biofilms, as well as a multispecies biofilm consisting of these two organisms in addition to Enterococcus faecalis ( E. faecalis ). As wound biofilms often exist in hypoxic wound environments, a direct contact anaerobic model system was used to evaluate efficacy on Bacteroides fragilis ( B. fragilis ). Biofilm control was evaluated against P. aeruginosa in the drip flow bioreactor model, where a constant flow of proteinaceous media is used to create a more challenging and wound‐like model. The results demonstrated that biofilm management capabilities varied amongst wound dressings. Two dressings, a controlled‐release iodine foam dressing and a silver nanocrystalline dressing, showed potent >4 log reductions in recovered organisms compared with untreated controls in all biofilm models evaluated. The effectiveness of other dressings to manage bioburden varied between dressing, test organism, and model system. A silver foam dressing showed moderate biofilm control in some models. However, biofilm exposure to methylene blue and gentian violet‐containing foam dressings showed negligible log reductions in all in vitro biofilm methods examined. The data outlined in this in vitro study support the use of the iodine foam dressing for wounds with infection and biofilm.